Iowa RBA, November 9, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Iowa RBA for November 9, 1998. Highlights include Lesser Black-backed Gull, Black-headed Gull, Surf Scoter, and White-winged Scoter. Includes notes for updates for November 10, November 11, November 12, and November 14. Epson - sheet feed/flatbed